Graph-based generation of a meta-learning search space - Jankowski, Norbert (Zielona Góra: Uniwersytet Zielonogórski)
Meta-learning is becoming more and more important in current and future research concentrated around broadly defined data mining or computational intelligence. It can solve problems that cannot be solved by any single, specialized algorithm. The overall characteristic of each meta-learning algorithm mainly depends on two elements: the learning machine space and the supervisory procedure.
Keywords: meta-learning; data mining; learning machines; complexity of learning; complexity of learning machines; computational intelligence